2012
DOI: 10.5530/pj.2012.30.10
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Muntingia calabura Fruits

Abstract: mechanism or action is known. [3] Many herbal preparations are being prescribed widely for the treatment of inflammatory conditions. [4] There is a need for research and developmental work in herbal medicine because apart from the social and economic benefits, it has become a persistent aspect of present day health care in developing countries. Plant secondary metabolites have provided an important source of drugs since ancient times and now around half of the practical drugs used are derived from natural sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
0
20
0
11
Order By: Relevance
“…A number of medicinal plants have been shown to offer an alternative to synthetic drugs in preventing and treating some chronic and mild diseases. The facts that synthetic and chemical therapeutic approaches possess severe adverse effects have triggered the search for natural products with less or, possibly, no side effect (Preethi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of medicinal plants have been shown to offer an alternative to synthetic drugs in preventing and treating some chronic and mild diseases. The facts that synthetic and chemical therapeutic approaches possess severe adverse effects have triggered the search for natural products with less or, possibly, no side effect (Preethi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As comparison, the people of Philippines used the flowers to treat headache and incipient cold while the people of Colombia used the flowers as a tranquillizer and tonic. With regard to the route of administration used, the in vivo studies described above used various ways to administer the extracts such as oral (acute toxicity, antiulcer, antidiabetic, and antinociceptive) (Ibrahim et al, 2012;Sridhar et al, 2011;Yusof et al, 2011), subcutaneous (antinociceptive, anti-inflammatory, and antipyretic) (Zakaria et al, 2006a(Zakaria et al, , 2007a(Zakaria et al, ,b, 2008, intraperitoneal (antinociceptive and anti-inflammatory) (Preethi et al, 2012;Sani et al, 2012), intravenous (hypotensive and cardioprotective) (Nivethetha et al, 2009;Shih et al, 2006Shih et al, , 2009. Taking into account that most medicinal plants are consumed orally, only investigations on the acute toxicity, antiulcer, antidiabetic, and antinociceptive activities were found to emulate the traditional ways of consuming medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the studies published on the proven effectiveness of organic and/or aqueous extracts from the leaves and flowers of M. calabura, reports about the biological action of organic extracts from the fruits and flowers against P. xylostella are lacking. The chemical composition of M. calabura plant is already known and the leaves have been shown to contain flavonoids, chalcones, terpenoids and phenolic compounds (Preethi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…leaves exhibit a range of pharmacological activities, that is protection against gastric damages (Zakaria et al, 2014;Balan et al, 2015), antibacterial and cytotoxic activities (Sufian et al, 2013) and antinociceptive activity ; and significant antioxidant activity, with a number of phenolic compounds identified (Kolar et al, 2011;Preethi et al, 2012;Zakaria et al, 2014;Balan et al, 2015). leaves exhibit a range of pharmacological activities, that is protection against gastric damages (Zakaria et al, 2014;Balan et al, 2015), antibacterial and cytotoxic activities (Sufian et al, 2013) and antinociceptive activity ; and significant antioxidant activity, with a number of phenolic compounds identified (Kolar et al, 2011;Preethi et al, 2012;Zakaria et al, 2014;Balan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have described that M. calabura Linn. leaves exhibit a range of pharmacological activities, that is protection against gastric damages (Zakaria et al, 2014;Balan et al, 2015), antibacterial and cytotoxic activities (Sufian et al, 2013) and antinociceptive activity ; and significant antioxidant activity, with a number of phenolic compounds identified (Kolar et al, 2011;Preethi et al, 2012;Zakaria et al, 2014;Balan et al, 2015). reported that calabura pulp is also a good source of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%